"Does training in Motivational Interviewing affect the ability to build working alliance? – an intervention study". Issue 1 (1st January 2019) - Haugan, Paula Sofie; Berge, Maria Charlotte; Breiseth, Vegard; Sund, Erik R.; Hedlund, Marianne
ABSTRACT: Higher education in health science and social work are examples of professional educations were it is vital to continue to learn and develop professional knowledge. This study focused on a specific education program which is of relevance to such professionals. Professional studies in health and social work demand insight into and knowledge of disciplines that embrace physical and mental health, as well as social issues. The aim of this study was to find out whether training in Motivational Interviewing contributed to the development of the ability to build a working alliance. N = 72 students within health and social work were surveyed with the Working Alliance Inventory, a questionnaire on thoughts and feelings in relation to clients (Horvath & Greenburg, 1989). They were surveyed (in 2014 and 2015) before and after a 1-year course in MI, and 73.6% (53/72) responded at both measurement points. Analyses were conducted both on each item (Wilcoxon matched-pairs signed ranks test) and on the three sub-scales: goals, tasks and bonds (paired samples t-test). The study showed no significant association between training in MI and increased the ability to build working alliances; however, an association between training in MI and decreased scoring on the sub-scale, goals, was found.